FACTORS RELATED MUSCULOSKELETAL DISORDERS ON STUDENTS OF UDAYANA UNIVERSITY ON 2016 - Made Adhyatma Prawira; Ni Putu Nita Yanti; Endri Kurniawan; Luh Putu Wulandari Artha (Universitas Darussalam Gontor, 2017)
Musculosceletal Disorders (MSDs) or musculosceletal’s problems are series of pain on muscle, tendon, and nerve. Those problems can decrease the work productivity. In Indonesia based on previous research, that was conducted at 12 cities or regencies, 16% of workers complained about MSDs. The purpose of this researched was evaluated the factors related to musculosceletal disorder among students of Faculty of Public Health, Udayana University. This study was quantitative research with cross sectional design. 72 students as samples were taken by non probability sampling method, with purposive sampling technique. The data was analysed by univariate analysis to describe distribution, by bivariate analysis to analyse variable association, and then by multivariate analysis with logistic regression to evaluate variabel that most influential. It was found that 66,7% students had musculosceletal complaint, consist of 85,42% females and 14,58% males. Highest complaint according to Nordic Body Map method was on the part of back 59,73%, on the nape of neck 50%, and on the part of neck 48,61%. According to the result of bivariate test, variables such as sex, exercise intensity, duration of sitting, body mass index (BMI), and anthropometry 8 did not show any association with musculosceletal complaint with by p value > 0,05. According to goodness of fit test the p value=0,764 (p>0,05), age (p<0,016), exercise intensity (p<0,026), ergonomic risks (p<0,024), and anthropometry 12 (p<0,003) had association with musculosceletal complaint and fit with logistic regression test. As conclusion of this research found that factors related with muscolusceletal disorder among Public Health students of Udayana University were age, exercise intensity, ergonomic risks, and anthropometry 12.Keyword: Musculosceletal Disorders; Public Health; Occupational Disease